De olho em Tomás de Aquino: uma contribuição tomasiana para a trajetória das paixões. - Gulke, Pedro Luiz Rodarte (2021)
In this dissertation, the adoption of Thomistic terms by rhetorical discourse analysts is proposed. Specifically, it is argued that the Thomistic terms that describe human perception can assist in the description of a passionate reaction, even in a rhetorical context, especially in the stages of the passionate reaction that precede the psychophysical changes already defined and described by Aristotle in the work The Rhetoric. A comparative study was carried out between Aristotelian rhetoric, as understood by modern analysts, and Aquinas´ treatise on the passions, with a focus on the steps that precede the emotional reaction, which would be, as described by Figueiredo (2018; 2020), availability and identification. It is noticed that there is a consonance between the way Aquinas describes the nexus between the sensitive faculty and the appetitive faculty and the first stages of the Pathway of Passion of Figueiredo (2020). For this reason, it is argued that the Thomistic metalanguage that describes the perception that precedes a passionate reaction can be used in a rhetorical analysis to describe pathos, specifically, to understand and describe what precedes and allows a certain passionate reaction on the part of the auditorium. Keywords: Rhetoric; Pathos; Sensitive Appetite; Pathway of Passions; Thomas Aquinas.